Undisputed Claim - Ali Ghesmati Tabrizi; Mohammad Sadegh Mehrabi Sisakht (مطالعات فقه و حقوق اسلامی, 2020)
Unlike the common belief that conflict is necessity for a claim, "undisputed claims" proceed without any conflict in order to confirm and stablish the defendant's claim. Along with jurisprudential background and numerous examples, some legal and social requirements warrant acceptance of this claim. Therefore it´s more appropriate to extend the title of "undisputed claims" beyond the pre-formed templates to any case that does not conflict with the defendant's rights. Acceptance criteria of this claim is defendant's rights that shows judicial decision is the most appropriate way to confirm and enforce plaintiff's rights. Despite the similarity with other judicial decisions, undisputed claim is an independent nature whose recognition has numerous practical implications in relation to plaintiff and the court. However, it is clear that acceptability of "undisputed claim" and identifying all plaintiff´s rights cannot hurt the rights of third parties.